OBESITAS TERHADAP KEJADIAN HIPERTENSI PADA USIA DEWASA (LITERATURE REVIEW) - Devi Marlina (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2024)
The development of technology, advancements in scientific knowledge, and the growing economy have significantly contributed to a sedentary lifestyle among the populace. Poor consumption patterns, such as indulging in high-calorie and high- fat foods, also serve as reasons for the rising cases of obesity. Hypertension is a condition characterized by a chronic increase in blood vessel pressure. This leads to the heart working harder to pump blood to meet the body's oxygen and nutrient needs. The coexistence of obesity and hypertension is prevalent, with the prevalence of hypertension accompanied by obesity continually increasing. Objective: To analyze the relationship between obesity and the occurrence of hypertension in adults. The research method employed in this study is a literature review, with selected articles using keywords such as obesity and hypertension from Google Scholar and PubMed in both Indonesian and English languages. Research findings indicate a correlation between obesity status and the occurrence of hypertension in adults. The conclusion drawn from this research is that the higher an individual's obesity level, the greater the likelihood of developing hypertension.